Biodegradation of plastics by white-rot fungi: A review (2023)
ABSTRACT: Plastic pollution is one of the most environmental problems in the last two centuries, because of their excessive usage and their rapidly increasing production, which overcome the ability of natural degradation. Moreover, this problem become an escalating environmental issue caused by inadequate disposal, ineffective or nonexistent waste collection methods, and a lack of appropriate measures to deal with the problem, such as incineration and landfilling. Consequently, plastic wastes have become so ubiquitous and have accumulated in the environment impacting ecosystems and wildlife. The above, enhances the urgent need to explore alternative approaches that can effectively reduce waste without causing harsh environmental consequences. For example, white-rot fungi These fungi produce ligninolytic enzymes able to break down the molecular structures of plastics, making them more bioavailable and allowing their degradation process, thereby mitigating waste accumulation. Over the years, several research studies have focused on the utilization of white-rot fungi to degrade plastics. This review presents a summary of plastic degradation biochemistry by white-rot fungi and the function of their ligninolytic enzymes. It also includes a collection of different research studies involving white-rot fungi to degrade plastic, their enzymes, the techniques used and the obtained results. Also, this highlights the significance of pre-treatments and the study of plastic blends with natural fibers or metallic ions, which have shown higher levels of degradation. Finally, it raises the limitations of the biotechnological processes and the prospects for future studies.